Mourning, Melancholy, and Humor: Psychotheology in Freud and Söderblom1. Issue 4 (4th December 2017) - Sigurdson, Ola
Abstract: This article aims at exploring the means for and hope of overcoming trauma, that is, violent emotional shock, through the use of humor and theology in conjunction. Both humor and the experience of the hope of some kind of redemption are ways of transcending the given. But is such overcoming possible without illusion or escapism? These issues are explored through the psychotheological perspectives on humor in the psychoanalyst Sigmund Freud and the Swedish archbishop and theologian Nathan Söderblom.